2022
DOI: 10.1002/acn3.51507
|View full text |Cite
|
Sign up to set email alerts
|

Younger age of stroke in low‐middle income countries is related to healthcare access and quality

Abstract: Stroke is the second leading cause of mortality globally with higher burden and younger age in low‐middle income countries (LMICs) than high‐income countries (HICs). However, it is unclear to what extent differences in healthcare access and quality (HAQ) and prevalence of risk factors between LMICs and HICs contribute to younger age of stroke in LMICs. In this systematic review, we conducted meta‐analysis of 67 articles and compared the mean age of stroke between LMICs and HICs, before and after adjusting for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 89 publications
2
13
0
1
Order By: Relevance
“…The clinical profiles of patients who received care at the LTSC facility revealed that the average age of stroke occurrence was 57.68 years ± 12.04. Although this age was below the global average for stroke, which was reported as 64.4 years (16), it corresponded to the recent mean age for stroke prevalence in Malaysia (54.5 - 62.6 years old) (17). This finding mirrored the current scenario in Malaysia, where stroke affects a much younger population compared to western countries.…”
Section: Discussionmentioning
confidence: 72%
“…The clinical profiles of patients who received care at the LTSC facility revealed that the average age of stroke occurrence was 57.68 years ± 12.04. Although this age was below the global average for stroke, which was reported as 64.4 years (16), it corresponded to the recent mean age for stroke prevalence in Malaysia (54.5 - 62.6 years old) (17). This finding mirrored the current scenario in Malaysia, where stroke affects a much younger population compared to western countries.…”
Section: Discussionmentioning
confidence: 72%
“…An earlier age of onset is also evidenced in lowmiddle-income countries compared with high-income countries, regardless of sex, stroke subtype, and whether data were collected at the population or hospital level (37)(38)(39)]. This age variability of stroke occurrence could be explained by healthcare access and quality (40)] and could be attributed to the early onset of stroke risk factors such as hypertension in the DRC and elsewhere in Africa ( 41)].…”
Section: Discussionmentioning
confidence: 99%
“…21,22 The study of researchers 23 even noted that conducting a community-based intervention with exercise and counseling sessions for 6 months significantly enhanced the physical fitness scores and self-care behaviors of patients with hypertension. 23,24 It should be noted, however, that lifestyle modifications should be tailor-fit and should be devised in consultation with the patient. By making these modifications fit to the patient, they can adhere to such changes based on their daily activities, and the factors that may lead to non-adherence can be mitigated.…”
Section: Discussionmentioning
confidence: 99%